2018 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2018
DOI: 10.1109/iros.2018.8594290
|View full text |Cite
|
Sign up to set email alerts
|

A Confidence-Based Shared Control Strategy for the Smart Tissue Autonomous Robot (STAR)

Abstract: Autonomous robotic assisted surgery (RAS) systems aim to reduce human errors and improve patient outcomes leveraging robotic accuracy and repeatability during surgical procedures. However, full automation of RAS in complex surgical environments is still not feasible and collaboration with the surgeon is required for safe and effective use. In this work, we utilize our Smart Tissue Autonomous Robot (STAR) to develop and evaluate a shared control strategy for the collaboration of the robot with a human operator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…In addition, real-time predictions are also being made with recurrent neural networks (39). Conventional surgical robots are operated by a physician; however, surgical robots that work automatically without operation by a physician are also being developed (40). Thus, the development of AI has also led to the development of robots that support physicians during surgery.…”
Section: Current Ai Applied In Medicinementioning
confidence: 99%
“…In addition, real-time predictions are also being made with recurrent neural networks (39). Conventional surgical robots are operated by a physician; however, surgical robots that work automatically without operation by a physician are also being developed (40). Thus, the development of AI has also led to the development of robots that support physicians during surgery.…”
Section: Current Ai Applied In Medicinementioning
confidence: 99%
“…The linear blending approach also increases efficiency; Saeidi et al demonstrated in [345] that a 2D-pattern cutting task with partial blood occlusion could result in a work time diminution compared to a fully manual task. This experiment highlighted the interest of a confidence-based shared control strategy with an adaptive blending.…”
Section: Linear Blendingmentioning
confidence: 99%
“…Continuous Hidden Markov Model (CHMM) was used to learn surgeon's movement and automatically generate trajectories when performing a surgery. Saeidi et al [14] proposed a shared‐control strategy, which had a confidence evaluation model for the manual control and autonomous control. The most reliable source of control would be given the full control weight.…”
Section: Introductionmentioning
confidence: 99%
“…The adjustment of shared‐control weights is achieved through online assessment of surgeon's skill level and dynamic weight allocation to enable the robot autonomy to assist a surgeon properly. The weights will be adjusted progressively between 0 and 1 to eliminate the effects of switching among surgical operations [14].…”
Section: Introductionmentioning
confidence: 99%